The practices of heat adaptation among elderly in Dezful: A qualitative study - Hamidreza Aghababaeian; Abbas Ostadtaghizadeh; Maryam Kiarsi; Hossein Sarfaraz; Ladan Aragi Ahvazi; Mohammad Maniey (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Useful experiences of the elderly in adapting to the environment may play an important role in formulating future policies. This study was conducted to explain the past experiences of the elderly in Dezful in adapting to heat. MATERIALS AND METHODS: This study was conducted with a qualitative research approach and a qualitative content analysis method in 2020 and 2021. The experiences of 18 elderly in Dezful were collected through semi-structured interviews via recording, face-to-face interviews, and data observation. Sampling was performed by the purpose-based method, and the data of this stage were analyzed using a content analysis approach using the Zhang and Wildemuth method. RESULTS: During the data analysis process, three main themes were extracted, including psychophysiological, socioeconomic, and environmental adaptation. Also, twelve subthemes including changes in physiological conditions, urban architecture, house architecture, diet, clothing, business conditions, mindset, life conditions, and the use of factors (spirituality, experience, and natural capacities) were extracted. CONCLUSION: Explaining the experiences of the elderly in Dezful, who have lived with heat for many years, can provide better identification of solutions and more tangible experiences of adaptation to heat for other communities. These experiences can be used in urban, cultural, and social planning.